A comparative histological study on the effect of exposure to the smoke leaf extract of tobacco nicotiana, cannabis sativa and datura stramonium on the lungs of sprague-dawley rats - A. Adekomi, D.; A. Tijani, A.; M. Afodun, A.; K. Quadri, K. (Scientific Journal of Medical Science, 2012)
Smoking may exert compromising effects on several organ systems of the body, but those in the lungs are the most deleterious. Therefore the aim of the present study was to investigate some of the effects of inhalation of smoke extract of Tobacco nicotiana (Tobacco), Cannabis sativa and Datura stramonium (Jimson Weed) on the respiratory system, especially on the lungs. Twenty male Sprague Dawley rats were divided into four groups A-D. The rats in the control group (A) were not subjected to any of the smoke extracts, while the rats in groups B, C, and D were exposed to smoke from a completely burnt 0.74g leaf extract of Tobacco nicotiana, Cannabis sativa and Datura stramonium each for 5 minutes three times daily (7am, 10am, and 1pm) respectively. The duration of exposure in all the groups was for five days. All the rats were sacrificed by decapitation and the lung tissues were obtained from each animal using thoracotomy, blotted dry and fixed in buffered neutral formalin for histopathological analysis using Hematoxylin and Eosin (H&E) stain. In the lung tissue of the rats in the control group (A), the histological profile of the lungs were preserved, whereas in groups B, C, and D the histological outline of the tissues obtained revealed disruptive characteristics such as emphysema, evidence of bronchopneumonial features and fibrosis, occlusion of the bronchi, and dilation of the alveoli sac. In conclusion, the exposure of male Sprague Dawley rats to the smoke extract of Tobacco nicotiana (Tobacco), Cannabis sativa and Datura stramonium (Jimson Weed) has compromising effects on the histological integrity of the lungs of the rats and by extension may cause irreversible functional and morphological alterations in the lung tissue.